2021
DOI: 10.3389/fmed.2021.648675
|View full text |Cite
|
Sign up to set email alerts
|

Remote Management of Prosthodontic Emergencies in the Geriatric Population During the Pandemic Outbreak of COVID-19

Abstract: The global pandemic outbreak of coronavirus disease 2019 (COVID-19) has put the world in a panic situation. It has been evident that the geriatric population is more susceptible to acquire this infection. Thus, due to this ongoing crisis, geriatric individuals cannot visit a dental operatory, and there is the possibility of their dental needs and emergencies to remain unattended. Partial or complete edentulism is very prevalent among the geriatric population, and prosthodontic management of these patients is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Prosthodontic emergencies in this population during the crisis should include reassurance, motivation, following patients remotely and adopting teledentistry or mobile dentistry. 7 The use of disposable or single-use instruments and double covering for sensors while shooting radiographs can be additional measures along with standard preventive measures. Repair of broken dentures needs to be considered in cases of pain and discomfort.…”
Section: Prosthodontic Care In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Prosthodontic emergencies in this population during the crisis should include reassurance, motivation, following patients remotely and adopting teledentistry or mobile dentistry. 7 The use of disposable or single-use instruments and double covering for sensors while shooting radiographs can be additional measures along with standard preventive measures. Repair of broken dentures needs to be considered in cases of pain and discomfort.…”
Section: Prosthodontic Care In Covid-19mentioning
confidence: 99%
“…Cases of hyperplastic tissue associated with the removable prosthesis or implant overdenture should be managed with topical astringents and local anaesthesia and surgeries should be deferred until the pandemic resides. 7 Elderly patients with poor oral hygiene and systemic conditions are more prone to develop oral candidiasis. This situation in a COVID-19 patient impacts negatively by increasing morbidity.…”
Section: Prosthodontic Care In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…They performed a minireview aiming at discussing the common prosthodontic emergencies and providing recommendations for this social category. The authors concluded that, during the pandemic period, TD might be considered in case of all prosthodontic situations, emergencies, or non-emergencies, followed by portable/mobile dentistry; however, the use of personal protection equipment (PPE) in order to avoid any potential transmission if COVID-19 should be mandatory [49].…”
Section: The Use Of Teledentistry For Geriatric Populationsmentioning
confidence: 99%
“…Teledentistry allows dental clinicians to provide consultation, make the provisional diagnosis, treatment planning, prescribe medications, advise referrals and educate patients about the importance of oral health care without actually meeting the patient in person ( Deshpande et al, 2021 ; Santana et al, 2020 ; Nassani et al, 2021 ). The major advantage of teledentistry is that it permits minimum attendance in clinical settings thus reducing the risk of COVID transmission ( Aldhuwayhi et al, 2021 ). This is of paramount importance, particularly for the clinician and patient protection.…”
Section: Introductionmentioning
confidence: 99%